Does Corporate Governance Improve Small-Firm Performance? The Mediating Role of Organizational Culture - Diaz Peláez, Alejandro; Clemente-Almendros, José Antonio; Londoño-Toro, Carlos Mario; Alarcón-Nieto, Camilo; Salgado Herrera, Raquel Patricia (Studies in Business and Economics, 2026)
This study examines how organizational culture helps corporate governance positively influence the performance of small companies. Using a primary database of small companies in Medellín, we develop a Structural Equation Model. Our results show that, on its own, corporate governance is not sufficient to positively influence the performance of small companies. It needs the mediating effect of organizational culture. These findings help to understand the sometimes inconclusive evidence of the inclusion of governance policies in small organizations. Moreover, our proof paves the way for managers and policymakers to develop specific policies that increase the performance of this type of organization.
Keywords: corporate governance; strategy; business value; performance; organizational culture